ANALYSIS OF FACTORS INFLUENCING INCOME FROM RICE (Oryza Sativa L.) FARMING IN PANGARIBUAN DISTRICT, NORTH TAPANULI DISTRICT, NORTH SUMATRA PROVINCE - Waty Marlinang Pakpahan; Adelina Lubis; Buhari Sibuea (RADJA PUBLIKA, 2024)
Rice farming income is the difference between revenue and all costs of rice farming. This study aims to identify and analyze the factors that influence the income of lowland rice farming in Pangaribuan District, North Tapanuli Regency, North Sumatra Province. The type of research used in this research is quantitative research. The population used in this study were lowland rice farmers in Pangaribuan District, North Tapanuli Regency, North Sumatra Province with a total sample of 80 lowland rice farmers. The data analysis method used is multiple linear regression analysis. The results of the research show that the real income received by rice farmers in Pangaribuan District, North Tapanuli Regency tends to increase with an average income of around Rp. 35,230,000/year. The average income received is IDR 20,100,000 – IDR 30,000,000 per harvest, the average land area is 0.5-0.7 per hectare, the average selling price is IDR 10,000. – IDR 11,000 per harvest, average capital IDR 10,100,000 – IDR 15,000,000 per production, average labor 1-3 people, use of fertilizer using urea fertilizer and average production costs IDR 3,100,000. – Rp. 5,000,000 per production. Partially, land area, selling price, production results, capital, labor, fertilizer and production costs have a significant effect on the income of lowland rice farming in Pangaribuan District, North Tapanuli Regency, North Sumatra Province. Simultaneously, land area, selling price, production results, capital, labor, fertilizer and production costs have a significantly significant effect on the income of lowland rice farming in Pangaribuan District, North Tapanuli Regency, North Sumatra Province..